News Media Literacy-Inquiry into the Current Situation of Taiwan's Media Environment and Policies - Hsieh Tsung-Shun, Huang Chao-Hsi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The proliferation of false information and fake news has led to a decline in global news trust. Taiwan's news trust in Taiwan is only slightly higher than that of France (23%) and South Korea (21%) (Newman, Nic, Richard Fletcher, Anne Schulz, Simge AndRasmusKleis Nielsen, 2020; He Hui'an,2020).Under Taiwan's liberal and democratized system, freedom of speech and the vigorous development of the media environment are guaranteed. Taiwan’s communication ecology originally suffered from vicious competition from commercial media and lacked a solid public media system. Although martial law was lifted and the media opened up, it was able to enjoy a high degree of freedom of communication. However, for more than 30 years, the competitive order has not been effectively established. As a result, Chinese people have repeatedly criticized the quality of news and media content (National Communications Commission, 2020). This article will use literary analysis and data investigation to explore the global active fight against fake news and promote media literacy in the context of consensus to deconstruct the influence of fake news on Taiwan, covering the number of media outlets and the competitive environment, and the National Communications Commission’s influence on the media and fake news. Management and promotion of media literacy policies.